Milk and dairy products : properties and processing - Rosenthal, Ionel (New York, NY, USA : VCH ; Israel : Balaban Publishers, 1991)
This book is a condensed, up-to-date and well-structured compilation of the key knowledge in the field. It covers the chemical properties of milk, milk in its biological context, processing operations specific to dairy industry and manufacture of dairy products.
Includes bibliographical references and index.
1
Keywords: Dairying; Milk; Dairy products